2005
DOI: 10.1016/j.femsim.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 negatively regulatesPorphyromonas gingivalisfimbria-stimulated fibronectin expression in human gingival fibroblasts

Abstract: Our previous study demonstrated that fibronectin (FN) is a negative regulator of Porphyromonas gingivalis fimbria-induced pathogenesis in the initiation and development of chronic periodontal diseases. We show herein the regulatory action of interleukin-6 (IL-6) on FN expression in fimbria-treated human gingival fibroblasts. Interestingly, the decrease in FN expression in the cells treated with fimbriae at a high dose (8 microg of protein ml(-1)) was negated by treatment with anti-IL-6 antibody. Also, the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Moreover, Kawata et al have observed that fimbria-stimulated bone resorption is inhibited by pretreatment with FN [35]. In addition, we have observed that FN is negatively regulated by fimbria-stimulated endogenous interleukin-6 and that the amount of FN in gingival crevicular fluid is decreased in patients with severe periodontal disease [36]. These observations suggest that FN might play a functional role as a negative regulator of fimbria-mediated pathogenesis in the initiation and development of chronic periodontal disease.…”
Section: Fibronectinmentioning
confidence: 88%
“…Moreover, Kawata et al have observed that fimbria-stimulated bone resorption is inhibited by pretreatment with FN [35]. In addition, we have observed that FN is negatively regulated by fimbria-stimulated endogenous interleukin-6 and that the amount of FN in gingival crevicular fluid is decreased in patients with severe periodontal disease [36]. These observations suggest that FN might play a functional role as a negative regulator of fimbria-mediated pathogenesis in the initiation and development of chronic periodontal disease.…”
Section: Fibronectinmentioning
confidence: 88%